Collateral damage - Eason, Lynette (Eason, Lynette. Danger never sleeps, 2020)
A former military psychologist spends her days helping vets overcome PTSD--and her nights fighting her own nightmares. Now, on the run with a client who has already saved her life twice, she must uncover powerful secrets before they both end up dead.